2003
DOI: 10.1021/ie020140c
|View full text |Cite
|
Sign up to set email alerts
|

De Wet Process for the Beneficiation of Zircon:  Optimization of the Alkali Fusion Step

Abstract: Milled zircon, d 50 ≈ 9 μm, was fused with caustic soda pearls in open reaction vessels at temperatures between 650 and 850 °C. Fusion times of 1, 2, 4, 24, and 336 h (with intermittent milling) were investigated. The fusion products were characterized by X-ray diffraction and by wet-chemical analysis. For prolonged fusion times, the fusion products approached equilibrium compositions. However, the phases Na2ZrSiO5 and Na4Zr2Si3O12 observed at 850 °C did not form at 650 °C. Because these compounds do not hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 5 publications
1
16
0
10
Order By: Relevance
“…El-Yamani et al [15] choose 650 • C and 60% of excess NaOH at 2 h as the optimum conditions and obtained 97.6% zircon decomposition but they used commercial grade sodium hydroxide. The complete dissociation observed by El-Barawy et al was also confirmed by the treatment of other zircon concentrate around the world as reported by Focke et al [11] for Richards Bay (South Africa) zircon, Saha and Chandran [16] for Indian zircon, and recently by Naher and Haseeb [17] for Bengaline zircon. All these workers used extensive reaction conditions and relatively small amount of zircon as a started reaction materials.…”
Section: Effect Of Temperatures and Zircon To Alkalis Ratiosupporting
confidence: 56%
See 2 more Smart Citations
“…El-Yamani et al [15] choose 650 • C and 60% of excess NaOH at 2 h as the optimum conditions and obtained 97.6% zircon decomposition but they used commercial grade sodium hydroxide. The complete dissociation observed by El-Barawy et al was also confirmed by the treatment of other zircon concentrate around the world as reported by Focke et al [11] for Richards Bay (South Africa) zircon, Saha and Chandran [16] for Indian zircon, and recently by Naher and Haseeb [17] for Bengaline zircon. All these workers used extensive reaction conditions and relatively small amount of zircon as a started reaction materials.…”
Section: Effect Of Temperatures and Zircon To Alkalis Ratiosupporting
confidence: 56%
“…The melting point of KOH is 406 • C [11], G for this reaction at 298 • K is expected to be more negative than that of reaction (2) and hence one can expect that the former has slightly more decomposition effect on zircon than NaOH. Therefore, when the mixed alkalis used, the competition of KOH is longer than that of NaOH, which mean that the molar percent of KOH may decrease than that of the eutectic ratio.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The chemical inertness of zircon renders its processing a difficult task, and a large number of studies were carried out on this problem; several methods are used for industrial processing of zircon, including chlorination [7][8][9], sodium hydroxide fusion [10][11][12][13][14][15][16][17], sodium carbonate fusion [11,12,17], mixed alkali fusion [18][19][20], liming fusion or other alkali metal oxides [21][22][23], sodium hydroxide solution leaching [24,25], fluorosilicate fusion [26], plasma thermal dissociation in the presence of carbon [27,28]. Alkali fusion with NaOH is the most commonly used method in China due to the advantages of technically simplicity and low reaction temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The production of pure zirconium dioxide through zircon fusion with alkali at temperatures between 600 and 850°C, [8][9][10] followed by wet chemical treatments can solve many problems at the first stage. The authors have studied these pyro-and hydro-metallurgical steps.…”
Section: Introductionmentioning
confidence: 99%